2012
DOI: 10.4025/actascianimsci.v34i2.11782
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition value of silage from corn hybrids in the State of Mato Grosso, Brazil - doi: 10.4025/actascianimsci.v34i2.11782

Abstract: ABSTRACT. Nutrition value of silage from corn hybrids produced in Mato Grosso, State was evaluated. A randomized block design was used with 23 treatments (hybrids) and three replications. The study used hybrids from different seed companies. Fodder was stored in PVC pipes at a density of 600 kg of green mass m -³. The silos were opened 90 days after ensiling, and the following variables were studied: pH, dry matter (DM), ammoniacal nitrogen (N-NH 3 ), crude protein (CP), acid detergent fiber (ADF), neutral det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
2
0
2
Order By: Relevance
“…The IVDMD values of unique corn silage were similar to those obtained by Domingues et al (2012), who evaluated different silages of various corn hybrids (second harvest crops) and found mean digestibility levels of 70.79%.…”
Section: Resultssupporting
confidence: 83%
“…The IVDMD values of unique corn silage were similar to those obtained by Domingues et al (2012), who evaluated different silages of various corn hybrids (second harvest crops) and found mean digestibility levels of 70.79%.…”
Section: Resultssupporting
confidence: 83%
“…The IVDMD values of monocropped corn silage were close to those obtained by Carvalho et al (2016) and Domingues et al (2012), who analyzed monocropped corn silages supplemented with forage peanuts and silages of different corn hybrids in the off-season and observed mean digestibility values of 746.71 and 707.90 g kg −1 , respectively. In contrast, Serbester et al (2015) reported a lower digestibility (606.53 g kg −1 ) in monocropped corn silage.…”
supporting
confidence: 89%
“…The development of these hybrids with a silage purpose has resulted in maize silage being a common food for cattle throughout the country. However, the choice of the most suitable hybrids has been the subject of discussions due to the scarcity of information on their qualitative aspects (Zeoula et al, 2003), which are highly relevant as they determines the quality of an animal's final diet (Domingues et al, 2012).…”
Section: Introductionmentioning
confidence: 99%